Effect of antimycotics and rifampicin on the pharmacokinetics of buprenorphine and the feasibility of sublingual fentanyl for procedural sedation - Fihlman, Mari (fi=Turun yliopisto|en=University of Turku|, 2020)
Buprenorphine and fentanyl are opioids, which have been clinically used for decades. Buprenorphine is traditionally prescribed for maintenance therapy in opioid dependent patients and to a lesser extent in the treatment of acute pain. Fentanyl is the most widely used perioperative opioid. In recent years new dosage forms have been introduced for both of these drugs. The use of buprenorphine in the treatment of chronic pain has increased with the introduction of sublingual and transdermal formulations. Good results have been obtained with the administration of sublingual fentanyl in the treatment of cancer breakthrough pain. Some interaction studies have been made using high-dose buprenorphine and antiretrovirals, but there are few studies evaluating the drug-drug interactions between low-dose buprenorphine and known CYP3A4 inhibitors and inducers. In this thesis three studies were conducted to study the interactions between buprenorphine, using three different administration routes, and two CYP3A4 inhibitors, voriconazole and posaconazole and the CYP3A4 inducer, rifampicin. Voriconazole increased significantly the plasma concentration of sublingually and orally administered buprenorphine. Posaconazole also increased the plasma concentration of sublingually administered buprenorphine but the effect was not as evident as that encountered with voriconazole. Rifampicin decreased the plasma concentrations of sublingually administered buprenorphine, but it had no effect after the opioid’s intravenous administration. The aim of the fourth study was to evaluate the efficacy and safety of a sublingually administered fentanyl tablet in patients having colonoscopy. Patients often experience colonoscopy painful and unpleasant. Intravenous sedation increases the costs of colonoscopy significantly because patients need monitoring during sedation and recovery. The use of the sublingual administration route could offer a cost-effective alternative to intravenous sedation. This study showed that 100 micrograms of sublingual fentanyl was ineffective for the treatment of pain during colonoscopy. Nonetheless, it was observed that very few procedures had to be interrupted and the pain that patients experienced was mostly moderate. This raises the question of whether we should treat patients for anxiety and distress instead of pain.